Reliability of remote at-home oscillometric blood pressure monitoring in community-dwelling children aged 3–17 - Ho, Emily H.; Ece, Berivan; Clingan, Caroline; Zola, Anne; Tuladhar, Zutima; Kupczyk, Magdalena Ewa; Adair, Linda S.; Gershon, Richard (Frontiers in Pediatrics, 2025)
BackgroundAs hypertension becomes more prevalent, remote assessment of blood pressure (BP) has been proposed as a method to improve BP management in the pediatric population. We investigated the reliability of at-home BP monitoring in children ages 3–17.MethodsThis study was conducted at six sites across the United States. Children participated in three BP measurements on one occasion by caregivers at home and, on another separate occasion, by trained examiners in a clinic setting. The results were averaged and classified according to the 2017 Pediatric Hypertension Guidelines as normal BP, elevated BP, stage 1 hypertension, or stage 2 hypertension. We collapsed participants with elevated BP, stage 1 hypertension, or stage 2 hypertension into one group: above-normal. We examined the agreement between the caregivers’ and examiners’ BP readings and the ease of the measurement process.ResultsOne hundred eighteen (118) children participated in this study (48.3% male; mean age 9.65 ± 4.52 years). Most caregivers (78%−93%) and examiners (88%−99%) rated elements of BP measurement as “easy” or “very easy”. Caregiver and examiners’ agreement on BP classification as normal or above-normal ranged from 75.00% to 90.16% across age groups. Caregiver and examiner BP concordance significantly differed by age group (p = .03) and was lower among children with above-normal BPs.ConclusionsOverall, most aspects of the remote BP measurement process were rated as easy, suggesting that remote monitoring of BP in children is feasible. Concordance of BP measurements by caregivers and examiners was high for children in the normal BP range. More research is needed on the reliability of home BP monitoring across the pediatric age range for those with above-normal BP.